A simulation-based investigation into the bidirectional charge and discharge dynamics in lead-acid batteries - Noor Zelan, Muhammad Aiman; Hidayat, Muhammad Nabil; Nik Ali, Nik Hakimi; Umair, Muhammad; Mohd Mawardi, Muhammad Izzul; Ahmad, Ahmad Sukri; Abdullah, Ezmin (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
This paper presents a comprehensive simulation-based investigation into the bidirectional charge and discharge dynamics of lead-acid batteries within electric vehicles (EVs) and energy storage systems (ESS). Utilizing a bidirectional DC-DC converter (BDC) integrated with a lead-acid battery, the study explores the performance of these batteries through various charging and discharging scenarios. The simulation model, implemented using MATLAB, assesses the impact of charging strategies on battery behavior, focusing on key metrics such as state of charge (SOC), energy performance, and charging rates. The results reveal that lead-acid batteries, when paired with appropriate charging infrastructure and strategies, demonstrate enhanced performance and reliability in both EV and ESS applications. The study highlights the significant role of BDC topology in facilitating efficient energy transfer and optimizing battery usage. The findings underscore the potential for improved performance and widespread adoption of bidirectional converters in sustainable energy solution.